PENGELOLAAN PENGETAHUAN BERBASIS KNOWLEDGE-BASED VIEW (KBV) MELALUI RKJM MENUJU GENERASI CERDAS, KREATIF, DAN BERAKHLAK MULIA DI UPT SMP NEGERI 4 TAPUNG - Abdul Hamid; Aini Nur Zam-zam; Ayu Rodiah; Deni Firmansyah; Fitria Roshi Ramadhani; Ika Martilla; Salva Cistia Ritonga; Sohiron (PT. Hasba Edukasi Mandiri, 2026)
This study examines school planning management based on education management principles in supporting the vision of UPT SMP Negeri 4 Tapung through the integration of RKJM (Medium-Term School Work Plan) and data-driven planning using the Education Report Card (Rapor Pendidikan). The background of this research is the importance of structured educational planning in improving school quality and achieving educational goals effectively. The purpose of this study is to analyze the implementation of school planning, the transition from RKJM to data-based planning, and its alignment with school management practices. This research uses a qualitative descriptive method through document analysis, interviews, and observations involving the school principal and related stakeholders. The results show that the school has shifted from traditional RKJM planning to a more adaptive Perencanaan Berbasis Data (PBD) approach based on Rapor Pendidikan. The planning system is implemented systematically, involving stakeholders such as teachers, school committees, and education authorities, and is aligned with school vision and available resources. The findings also indicate that Rapor Pendidikan plays a crucial role in determining program priorities and improving decision-making in school management. In conclusion, data-based planning strengthens school management effectiveness, improves transparency, and supports sustainable educational development.